Application of Periareolar Mammaplasty with the Tissue Folding Technique in Breast Reshaping following Polyacrylamide Hydrogel Removal - Cai, Yantao (Breast Care (Basel), 2020)
BACKGROUND: Polyacrylamide hydrogel (PAAG) was used as an injectable implant for augmentation mammoplasty for over 30 years, but its use was ceased due to various related complications. The only way to treat these complications is PAAG removal, but this causes breast ptosis, nipple retraction, breast asymmetry, and skin laxity. OBJECTIVES: This article reports a new technique for breast reshaping after PAAG removal without prosthesis implantation. METHOD: From January 2015 to June 2018, twenty-three patients underwent periareolar mammoplasty with the tissue folding technique (PMTFT) for breast reshaping after PAAG removal. Postoperative breast shape and the degree of satisfaction of the patients were evaluated during follow-up. RESULTS: All patients recovered well without severe complications. All patients were satisfied with their postoperative breast shape and their symptoms were relieved after surgery. CONCLUSIONS: PMTFT provides satisfactory postoperative breast shape results. Economical, practical, and technical advantages were found over traditional prosthesis-mediated breast reconstruction. PMTFT can be an ideal surgical choice in appropriate cases.